Cellulose-based composite material for simultaneously removing copper and tetracycline in water body and preparation method of cellulose-based composite material
By ultrasonic assisting in the synthesis of Zr-MOF on the surface of nanocellulose, the Zr-MOF/CNF composite material is formed, which solves the problem of efficient removal of copper and tetracycline in water, and achieves efficient adsorption and good recycling.
Patent Information
- Application Number
- CN202411826342.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The prior art is difficult to effectively remove copper and tetracycline in water, especially when the two coexist, and the agglomeration and water stability of MOF particles are poor, and the cellulose lacks a porous structure.
Ultrasonic assisted method is used to synthesize Zr-MOF in situ on the surface of nanocellulose (CNF) to form Zr-MOF/CNF composite material. By adjusting the mass ratio of Zr-MOF and CNF and the ultrasonic treatment conditions, the adsorption performance of the composite material is improved.
Highly efficient adsorption of copper and tetracycline in water bodies was achieved, with adsorption capacity reaching 157.08 mg/g and 1532 mg/g respectively, and the composite material has good recycling and stability, which improves the problems of MOF particle agglomeration and poor water stability.
Smart Images

Figure CN119633764A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental functional composite materials, and specifically relates to a Zr-MOF / CNF composite material for simultaneously removing copper and tetracycline from water and a preparation method thereof, and is mainly used in copper and tetracycline wastewater treatment. Background Art
[0002] Copper and tetracycline are widely added to feed to promote animal growth and treat diseases. Most of them cannot be absorbed by animals and are discharged into the natural environment with animal excrement. When the two pollutants coexist, they will form a more toxic complex, causing combined pollution of copper and tetracycline. The treatment methods for combined pollution of copper and tetracycline in water bodies mainly include physical methods (adsorption method, membrane separation method), biological methods (fixed microbial treatment method, anaerobic-aerobic combined treatment method) and chemical methods (electrochemical method, chlorination method, advanced oxidation technology). Among them, the adsorption method is increasingly attracting attention due to its advantages of high efficiency, low cost, simple operation and less secondary pollution.
[0003] Cellulose is the most abundant polysaccharide in nature, and it is known for its large aspect ratio, rich functional groups, excellent mechanical properties, good water stability, and good environmental friendliness. Metal-organic frameworks are three-dimensional porous organic-inorganic hybrid materials. They have rich porosity and extremely high specific surface area. The structure and size of MOF can be adjusted by changing the introduced organic ligands and different reaction conditions. Due to these advantages, MOF has been widely used in the field of water pollution control. Zr-based MOF has been shown to have excellent water stability, chemical stability, and wide pH adaptability, making it very suitable for underwater operating conditions. Our method deviates from the traditional solvothermal method and uses an ultrasonic method, which has received little attention in the field. MOF is synthesized in situ on CNF under ultrasound. At the same time, the introduction of CNF can provide a dispersion carrier for small MOFs, significantly reducing their agglomeration, and achieving a synergistic effect between the two.
[0004] In this context, we developed a general and effective strategy to load functional Zr-based MOF onto nanocellulose (CNF) and synthesize porous materials with good adsorption properties, namely Zr-MOF / CNF composites, using an ultrasound-assisted in-situ growth method. Zr-MOF / CNF composites can effectively remove copper and tetracycline while maintaining their structural stability in aqueous solution. The reusability of the composites for copper and tetracycline and their adsorption mechanism were also explored.
[0005] In the prior art, some results have been achieved in the preparation method of MOF / cellulose composite materials, such as Chinese Patent No. 202310622290.2, published on May 30, 2023, which discloses a patent document entitled "A MOF / cellulose hydrogel and its preparation method and application". This patent combines MOF into the matrix of the hydrogel, and self-assembles to produce a mesh nanofiber structure, which greatly improves the mechanical strength, fatigue resistance, self-healing and biocompatibility of the hydrogel. This preparation method is relatively complicated, and it is not yet known whether improving the mechanical strength of the hydrogel is feasible for adsorbents used to adsorb pollutants; Chinese patent application number: 202311400310.8, publication date February 27, 2024, discloses a patent document entitled "A carboxylated cellulose-based magnetic MOF material and its preparation method and application". This patent first uses a co-precipitation method to quickly prepare carboxylated cellulose-coated magnetic Fe3O4 in a normal temperature and pressure environment in one step, and then grows MOF on the surface of the carboxylated cellulose-coated magnetic Fe3O4 to obtain a carboxylated cellulose-based magnetic MOF for immobilizing pullulanase. This material has good environmental stability and recyclability. If it is developed as an adsorbent for pollutants, it will have wide applicability; Chinese patent application number: 202110812440.7, publication date October 8, 2021, discloses a patent document entitled "A method for preparing MOF-loaded aerogel for adsorbing VOCs". This patent first grafts modified nanocellulose, and then uses hydrothermal reduction, one-step cross-linking, freeze-drying and in situ synthesis to construct UIO-66-COOH-loaded three-dimensional graphene oxide composite aerogel, which is used to adsorb VOCs. The synergistic adsorption of the composite aerogel carrier and the loaded crystals increases the adsorption capacity while allowing the aerogel to quickly and reversibly adsorb a large amount of VOCs waste gas, which helps to deal with VOCs waste gas with complex composition environments, but the adsorption performance of pollutants in water is still unknown; Chinese patent application number: 202210520373.6, publication date August 23, 2022, discloses a patent document entitled "Preparation of a HP-UIO-66-NH2 / cellulose composite aerogel material and its application in CO2 adsorption". The patent first prepares microcrystalline cellulose hydrogel, and then grows MOF on the surface of the hydrogel to obtain HP-UIO-66-NH2 / cellulose composite aerogel for CO2 adsorption.This method attempts to solve the problems of MOF particle agglomeration and poor mechanical stability. It is not certain whether the mechanism of adsorbing CO2 can be applied to the adsorption of pollution in water; National Patent Application No.: 201810467766.9, Publication Date October 12, 2018, discloses a patent document entitled "A MOF-100 (Fe) / bacterial cellulose composite material and its preparation method and application". The patent first activates the bacterial cellulose membrane in an alkaline mixed solution to obtain an activated-bacterial cellulose membrane, and then prepares the MOF-100 (Fe) / bacterial cellulose composite membrane material by a cyclic oscillation method for the adsorption of organic pollutants such as diclofenac sodium. It has a good removal effect on PPCPs such as diclofenac sodium in natural water environments, but the adsorption and removal ability of copper and tetracycline is unknown.
[0006] There are already some patent documents for the research on the adsorption and removal of copper and tetracycline in water. For example, Chinese patent application number: 202410323544.5, published on May 28, 2024, discloses a patent document entitled "Preparation of peanut shell biochar and its adsorption method for copper ions and nickel ions in electroplating wastewater"; Chinese patent application number: 202410501489.4, published on August 6, 2024, discloses a patent document entitled "A steel slag-based molecular sieve adsorption material in A patent document entitled "Application of nylon 6 / chitosan-Fe nanofiber composite materials in the adsorption of tetracycline" was disclosed. The above patents mainly adsorb and remove single pollution of copper and tetracycline in water bodies, but do not involve binary composite pollution. Summary of the invention
[0007] In view of the defects and shortcomings of the existing technology for removing copper and tetracycline from water, the problems of MOF particle agglomeration and poor water stability, and the lack of porous structure of cellulose, the present invention provides a porous MOF and nanocellulose CNF composite material and a preparation method thereof, in order to solve the above shortcomings of the existing technology.
[0008] To solve the above problems, the present invention adopts the following technical solutions.
[0009] The present invention provides a cellulose-based composite material for simultaneously removing copper and tetracycline from water. The composite material is Zr-MOF / CNF, and MOF is synthesized in situ on the surface of CNF under the assistance of ultrasound, specifically comprising the following steps:
[0010] (1) Mixing Enteromorpha cellulose and water to form a suspension, and stirring magnetically until uniform dispersion; adding TEMPO and NaBr and stirring until completely dissolved, and then adding NaClO solution; controlling the pH at 10 by adding NaOH solution, and immediately adding anhydrous ethanol to terminate the reaction if the pH does not change within 15 minutes, and then filtering the oxidized cellulose and washing with distilled water until the pH value is neutral; ultrasonically vibrating the obtained nanocellulose suspension for 15 minutes, and freeze-drying to obtain CNF; the mass ratio of TEMPO to NaBr is 4:25.
[0011] (2) ZrCl4·8H2O and H3BTC are added to a mixed solution of DMF and formic acid, stirred to ensure uniform mixing, and then ultrasonically treated. The suspension is then centrifuged, and the supernatant is poured out and washed with deionized water and anhydrous ethanol, respectively, to remove residual ZrCl4·8H2O and H3BTC; the precipitate after centrifugation is then placed in a drying oven for drying; after complete drying, it is ground and sieved to obtain Zr-MOF; the molar ratio of ZrCl4·8H2O to H3BTC is 1:1.
[0012] (3) adding Zr-MOF and CNF into deionized water, and after ultrasonic treatment, placing the precipitate after centrifugation into a drying oven, and obtaining a Zr-MOF / CNF composite material after complete drying; the mass ratio of Zr-MOF to CNF is 10-0.1:1.
[0013] Furthermore, in step (2), the ultrasonic treatment is carried out under the following conditions: ultrasonic wave at 600W power and 70°C for 90 minutes.
[0014] Furthermore, in step (3), the mass ratio of Zr-MOF to CNF is 1:5.
[0015] Furthermore, in step (3), the ultrasonic treatment is carried out under the following conditions: ultrasonic treatment for 60 minutes at room temperature.
[0016] The cellulose-based composite material obtained by the preparation method can simultaneously remove copper and tetracycline from water.
[0017] The specific principle of the present invention is speculated as follows:
[0018] The adsorption mechanism of copper and tetracycline in water by Zr-MOF / CNF is that copper and tetracycline are first electrostatically attracted to the surface of Zr-MOF / CNF, then diffuse into the pores through the macroporous structure of Zr-MOF / CNF by particle diffusion, and finally -COOH on Zr-MOF / CNF adsorbs copper and tetracycline. In addition, it is speculated that the adsorption removal process is related to the interaction between copper complexes, protonated functional groups, and chelate bonds.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) In the Zr-MOF / CNF composite material of the present invention, the in-situ growth of MOF on the CNF surface provides more adsorption sites for the composite material, and the anchoring of MOF and nanocellulose both increases more porous structures, thereby promoting the adsorption of copper and tetracycline in water.
[0021] (2) The preparation process of the present invention is simple, and the composite material is synthesized by a simple ultrasonic method, which has low production cost, high adsorption efficiency, and a wide range of applicable conditions. At the same time, the problems of MOF particle agglomeration and poor water stability are improved, thereby improving the practical application ability of Zr-MOF / CNF.
[0022] (3) The Zr-MOF / CNF composite material of the present invention can effectively adsorb copper and tetracycline. When the initial concentrations of copper and tetracycline are 32 mg / L and 444 mg / L, respectively, and the initial solution pH is 7.0, the adsorption capacity of Zr-MOF / CNF for copper and tetracycline reaches 157.08 mg / g and 1532 mg / g, respectively. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a comparison chart of the adsorption of copper and tetracycline in water by Zr-MOF / CNF composite materials with different mass ratios (mass ratios are 10:1, 5:1, 1:1, 1:5, 1:10, respectively) prepared according to the preparation method shown in Examples 1-5 and Zr-MOF and CNF prepared in the comparative example;
[0024] As can be seen from the figure, the Zr-MOF / CNF composite material (mass ratio 1:5) prepared in Example 4 of the present invention has the best adsorption capacity for 0.1 mmol / LTC-Cu solution.
[0025] Figure 2 : is the effect of solution pH on the adsorption and removal of copper and tetracycline by the Zr-MOF / CNF composite material of Example 4 of the present invention (experimental conditions: tetracycline-copper concentration is 0.1mmol / L (2:1); adsorption temperature is 25°C; adsorption material dosage is 0.1g / L);
[0026] As can be seen from the figure, the adsorption effect of the composite material of Example 4 of the present invention on copper and tetracycline gradually increases as the pH increases from 2 to 7, and the adsorption amount reaches the highest when the pH is 7. After the pH is greater than 7, the adsorption amount gradually decreases.
[0027] Figure 3 This is an adsorption-desorption experimental diagram of the Zr-MOF / CNF composite material obtained according to Example 4 of the present invention;
[0028] As can be seen from the figure, the composite material of Example 4 of the present invention still retains a good adsorption capacity after four cycles, which verifies that the composite material has a good cyclic adsorption capacity. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments, but is not intended to be a specific limitation of the present invention.
[0030] Example 1
[0031] This embodiment provides a method for preparing Zr-MOF / CNF (the mass ratio of zirconium-based MOF to nanocellulose is 10:1), the method comprising the following steps:
[0032] (1) Preparation of nanocellulose: 1.000 g of Enteromorpha cellulose and water were mixed to form a suspension of a certain ratio (1:100, w / v), and magnetic stirring was applied until the suspension was uniformly dispersed. 0.016 g of TEMPO (2,2,6,6-tetramethylpiperidin-1-oxide) and 0.1 g of NaBr were added and stirred for 30 min until completely dissolved, and then 20 mmol of 13% (w / w) NaClO solution was added. Then, the pH was controlled at 10 by adding 0.5 M NaOH solution. If the pH did not change within 15 min, anhydrous ethanol was immediately added to terminate the reaction, and then the oxidized cellulose was filtered and washed with distilled water until the pH value was neutral. Then, the obtained nanocellulose suspension was ultrasonically shaken for 15 min and freeze-dried to obtain nanocellulose (CNF).
[0033] (2) Preparation of zirconium-based MOF: 3 mmol of ZrCl4·8H2O and 3 mmol of H3BTC were added to 30 mL of DMF and formic acid and stirred at 200 r·min. -1 After stirring for 20 min at a speed of 1000 rpm to ensure uniform mixing, the suspension was reacted at 70 °C at an ultrasonic power of 600 W for 90 min. -1 After centrifugation for 10 minutes, the supernatant was poured out and washed five times with deionized water and anhydrous ethanol to remove residual ZrCl4·8H2O and H3BTC. The centrifuged precipitate was then placed in a drying oven and dried at 60°C for 12 hours. After complete drying, it was ground with a mortar and sieved with a 100-mesh sieve to obtain Zr-MOF.
[0034] (3) Preparation of Zr-MOF / CNF: Under the assistance of ultrasound, 10 mg of Zr-MOF and 1 mg of CNF were weighed and added into deionized water. Ultrasonic treatment was performed at room temperature for 60 min. The precipitate after centrifugation was placed in a drying oven and completely dried to obtain a Zr-MOF / CNF composite material.
[0035] Example 2
[0036] This embodiment provides a method for preparing a Zr-MOF / CNF composite material (the mass ratio of zirconium-based MOF to nanocellulose is 5:1), the method comprising the following steps:
[0037] (1) The preparation of nanocellulose is the same as described in step (1) of Example 1.
[0038] (2) The preparation of zirconium-based MOF is the same as described in step (2) of Example 1.
[0039] (3) The preparation of Zr-MOF / CNF composite material was the same as step (3) in Example 1, except that 2 mg of nanocellulose was added.
[0040] Example 3
[0041] This embodiment provides a method for preparing a Zr-MOF / CNF composite material (the mass ratio of zirconium-based MOF to nanocellulose is 1:1), the method comprising the following steps:
[0042] (1) The preparation of nanocellulose is the same as described in step (1) of Example 1.
[0043] (2) The preparation of zirconium-based MOF is the same as described in step (2) of Example 1.
[0044] (3) The preparation of Zr-MOF / CNF composite material was the same as step (3) in Example 1, except that 10 mg of nanocellulose was added.
[0045] Example 4
[0046] This embodiment provides a method for preparing a Zr-MOF / CNF composite material (the mass ratio of zirconium-based MOF to nanocellulose is 1:5), the method comprising the following steps:
[0047] (1) The preparation of nanocellulose is the same as described in step (1) of Example 1.
[0048] (2) The preparation of zirconium-based MOF is the same as described in step (2) of Example 1.
[0049] (3) The preparation of Zr-MOF / CNF composite material was the same as that described in step (3) of Example 1, except that 50 mg of nanocellulose was added.
[0050] Example 5
[0051] This embodiment provides a method for preparing a Zr-MOF / CNF composite material (the mass ratio of zirconium-based MOF to nanocellulose is 1:10), the method comprising the following steps:
[0052] (1) The preparation of nanocellulose is the same as described in step (1) of Example 1.
[0053] (2) The preparation of zirconium-based MOF is the same as described in step (2) of Example 1.
[0054] (3) The preparation of Zr-MOF / CNF composite material was the same as step (3) in Example 1, except that 100 mg of nanocellulose was added.
[0055] Comparative Example 1:
[0056] This comparative example provides a method for preparing nanocellulose CNF, which comprises the following steps:
[0057] The preparation of nanocellulose is the same as described in step (1) of Example 1.
[0058] Comparative Example 2:
[0059] This comparative example provides a method for preparing Zr-MOF, which comprises the following steps:
[0060] The preparation of zirconium-based MOF is the same as described in step (2) of Example 2.
[0061] Copper and tetracycline adsorption experiments were conducted on Zr-MOF / CNF composite materials with different mass ratios prepared by the preparation methods shown in Examples 1-5 above (mass ratios were 10:1, 5:1, 1:1, 1:5 and 1:10, respectively) and CNF and Zr-MOF prepared in the comparative example. The dosage of the adsorbent was 0.1 g / L. The experiment used CuCl2 and tetracycline hydrochloride to self-mix copper and tetracycline wastewater, wherein the molar ratio of tetracycline to copper was 2:1, and the concentrations were 444 mg / L and 32 mg / L, respectively. The reaction pH was 7, the temperature was 25°C, and the time was 4h and 24h. The residual concentrations of copper and tetracycline were measured, and the adsorption amount was calculated. The experimental results are as follows: Figure 1 As shown, after 4 hours of adsorption, the adsorption of each material tended to be saturated, among which the Zr-MOF / CNF composite material with a mass ratio of 1:5 had the best adsorption effect, and the adsorption amounts of copper and tetracycline reached 1532 mg / L and 157.08 mg / L, respectively.
[0062] The test data show that the Zr-MOF / CNF obtained in Examples 1-5 of the present invention has a very significant adsorption efficiency for aqueous copper and tetracycline (as shown in Table 1).
[0063] Table 1 Experimental results of adsorption of copper and tetracycline in different embodiments
[0064]
Claims
1. A cellulose-based composite material for simultaneously removing copper and tetracycline from water, characterized in that: The composite material is Zr-MOF / CNF, and its preparation includes the following steps: (1) Mixing Enteromorpha cellulose and water to form a suspension, stirring magnetically until uniformly dispersed; adding TEMPO and NaBr and stirring until completely dissolved, and then adding NaClO solution; controlling the pH at 10 by adding NaOH solution, and immediately adding anhydrous ethanol to terminate the reaction if the pH does not change within 15 minutes; then filtering the oxidized cellulose and washing with distilled water until the pH value is neutral; ultrasonically vibrating the obtained nanocellulose suspension for 15 minutes, and freeze-drying to obtain CNF; The mass ratio of TEMPO to NaBr is 4:25; (2) adding ZrCl4·8H2O and H3BTC to a mixed solution of DMF and formic acid, stirring to ensure uniform mixing, and then ultrasonically treating the suspension, then centrifuging the suspension, pouring out the supernatant, and washing to remove the residual ZrCl4·8H2O and H3BTC; then drying the precipitate after centrifugation; and grinding and sieving after complete drying to obtain Zr-MOF; The molar ratio of ZrCl4·8H2O to H3BTC is 1:1; (3) adding the CNF obtained in step (1) and the Zr-MOF obtained in step (2) into deionized water, and after ultrasonic treatment, completely drying the precipitate after centrifugation to obtain a Zr-MOF / CNF composite material; The mass ratio of the Zr-MOF to CNF is 10-0.1:
1.
2. A cellulose-based composite material for simultaneously removing copper and tetracycline from water as claimed in claim 1, characterized in that: In step (2), the ultrasonic treatment conditions are: ultrasonic wave at 600W power and 70°C for 90 minutes.
3. The cellulose-based composite material for simultaneously removing copper and tetracycline from water as claimed in claim 1, characterized in that: In step (3), the mass ratio of Zr-MOF to CNF is 1:
5.
4. The cellulose-based composite material for simultaneously removing copper and tetracycline from water as claimed in claim 1, characterized in that: In step (3), the ultrasonic treatment is performed at room temperature for 60 minutes.
5. Use of the cellulose-based composite material as claimed in any one of claims 1 to 4 for simultaneously removing copper and tetracycline from water.
Citation Information
Patent Citations
A MOF-100(Fe) / bacterial cellulose composite material, its preparation method and application
CN108636368B
A preparation method of a composite adsorbent for removing tetracycline from wastewater
CN114405465B
Preparation of an HP-UIO-66-NH2 / cellulose composite aerogel material and its application in CO2 adsorption.
CN114933734A
A MOF / cellulose hydrogel and its preparation method and application
CN116751374B
Preparation method of peanut shell biochar and method for adsorbing copper ions and nickel ions in electroplating wastewater by using peanut shell biochar
CN118083973A